A coupled heat and mass transfer model of green roof with water storage layer. (1st May 2023) - Wang, Jun; Mei, Guoxiong; Garg, Ankit; Liu, Ning
Abstract: Water movement plays an important role in the heat transfer process in green roofs, especially in the presence of the water storage layer. However, previous heat and mass transfer models did not consider the effect of water storage layer on variations in water content. Based on the water balance model and heat transfer equations, a heat and mass transfer coupled model considering the water storage layer is proposed in this study. The model is validated using a green roof experiment. The thermal performance of an integrated green roof structure (IGR) without insulation is compared to a bare roof with an insulation layer. The observed and simulated temperatures for different structural layers of the green roof fit well, with the Nash coefficients ranging from 0.72 to 0.97. The average room temperature of the green roof IGR is approximately 1 °C lower and higher in summer and winter, respectively. Moreover, the average room temperature of the green roof was reduced by approximately 1 °C–2 °C depending on the depth of water storage layer enhancement (0–50 mm). The results showed that the green roof IGR has the potential to replace the extruded polystyrene and protection layers of a bare roof. The cooling effect of the green roof with a water storage layer in summer is enhanced by the higher latent heat of evapotranspiration. Highlights: A heat and mass transfer model considering green roof storage layer is proposed. Room temperature under integrated green roof structure is 1 °C lower than bare roof. Green roof surface latent heat is increased by adding a water storage layer. The cooling effect of green roofs is enhanced by a water storage layer.